Engineering the emission of broadband 2D perovskites by polymer distributed Bragg reflectors - Lova, Paola (2020)
Thanks to their broadband emission and solution processability, 2D hybrid perovskite materials are promising for the realization of large area and flexible lighting devices. The deposition of 2D perovskites, however, requires wide range solvents that are incompatible with commodity polymers used for structural support and light management. Here we demonstrate coupling of broad-emitting 2,2-(ethylenedioxy)bis(ethylammonium)PbCl4 perovskite with solution processed polymer distributed Bragg reflectors on both rigid fused silica and flexible polymer substrates. The optical functions of the chemically engineered perovskite were determined by ellipsometric measurements and used to design dielectric multilayer structures with photonic bandgap tunable over the entire visible range. The resulting photonic structures control directionality and spectral enhancement or suppression of the perovskite photoluminescence, in agreement with simple analytical optical models. These results pave the way to the development of a new generation of color-tunable light-emitting devices based on a single active material.